2012
DOI: 10.1152/ajpendo.00269.2012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of GPR119 receptor activity with endocannabinoid-like lipids

Abstract: The GPR119 receptor plays an important role in the secretion of incretin hormones in response to nutrient consumption. We have studied the ability of an array of naturally occurring endocannabinoid-like lipids to activate GPR119 and have identified several lipid receptor agonists. The most potent receptor agonists identified were three N-acylethanolamines: oleoylethanolamine (OEA), palmitoleoylethanolamine, and linoleylethanolamine (LEA), all of which displayed similar potency in activating GPR119. Another lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 33 publications
(54 reference statements)
4
76
0
Order By: Relevance
“…GPR119 demonstrates a highly localized pattern of expression within the gastrointestinal tract and pancreas (Lan et al, 2009;Lauffer et al, 2009;Soga et al, 2005) consistent with a role in metabolic function. Endogenous agonists for GPR119 are lipids such as oleoylethanolamine and 2-oleoyl glycerol, further supporting this role (Cornall et al, 2013;Hansen et al, 2011;Syed et al, 2012). Indeed, stimulation of GPR119 is strongly linked with glucose homoeostasis with a direct effect on insulin release from pancreatic β-cells, as well as an indirect effect on insulin signalling via glucagon-like peptide 1 (GLP-1) release from enteroendocrine cells (Chu et al, , 2007Soga et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…GPR119 demonstrates a highly localized pattern of expression within the gastrointestinal tract and pancreas (Lan et al, 2009;Lauffer et al, 2009;Soga et al, 2005) consistent with a role in metabolic function. Endogenous agonists for GPR119 are lipids such as oleoylethanolamine and 2-oleoyl glycerol, further supporting this role (Cornall et al, 2013;Hansen et al, 2011;Syed et al, 2012). Indeed, stimulation of GPR119 is strongly linked with glucose homoeostasis with a direct effect on insulin release from pancreatic β-cells, as well as an indirect effect on insulin signalling via glucagon-like peptide 1 (GLP-1) release from enteroendocrine cells (Chu et al, , 2007Soga et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…GPR119 is a class A G protein-coupled receptor (GPCR) that signals predominantly through cAMP via the stimulatory G-protein (Gα s ) (Lauffer et al, 2009;Syed et al, 2012). GPR119 demonstrates a highly localized pattern of expression within the gastrointestinal tract and pancreas (Lan et al, 2009;Lauffer et al, 2009;Soga et al, 2005) consistent with a role in metabolic function.…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative evidence suggests the existence of a putative third type of cannabinoid receptor ('CB3'), called GPR55 (Ryberg et al 2007, Sharir & Abood 2010. Interestingly, and adding complexity to the pharmacology of cannabinoids, it has been shown that these compounds might elicit response in other receptors, such as transient receptor potential vanilloid 1 (TRPV1), peroxisome proliferatoractivated receptors (PPARs) and GPR119 (Huang et al 2002, Sun et al 2006, Syed et al 2012.…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%
“…Analogously, for the 2-monoacylglycerol (MG) series, there are also homologs such as 2-oleoylglycerol (OG) and 2-linoleoylglycerol (LG). Most of these molecules do not directly bind to CB receptors but may enhance/modify the actions of ECs (entourage effect) ( 6 ) or display biological activities related to their interactions with other receptors such as GPR119 (OEA, POEA, LEA, 2-OG) ( 7,8 ), transient receptor potential vanilloid type 1 (TRPV1) (OEA), GPR55 (PEA), or PPAR-␣ (OEA) ( 9 ). Finally, two putative ECs, N-eicosapentaenoyl ethanolamide (EPEA) and N-docosahexaenoyl ethanolamide (DHEA), derived from the n-3 polyunsaturated fatty acids, are able to bind with low affi nity to the CB1 and CB2 receptors and may have biological signifi cance in the brain ( 10,11 ).…”
Section: Standard Solutionsmentioning
confidence: 99%